Theosophy across boundaries: transcultural and interdisciplinary perspectives on a modern esoteric movement - Krämer, Hans Martin; Strube, Julian (SUNY series in Western esoteric traditions, 2020)
"Demonstrates that Theosophy was part of a truly global movement and played an important role in the general histories of religion, science, philosophy, art, and politics"--